Burden of disease caused by otitis media: systematic review and global estimates. - Lorenzo Monasta; Luca Ronfani; Federico Marchetti; Marcella Montico; Liza Vecchi Brumatti; Alessandro Bavcar; Domenico Grasso; Chiara Barbiero; Giorgio Tamburlini (PLoS ONE, 2012)
Background Otitis media (OM) is a leading cause of health care visits and drugs prescription. Its complications and sequelae are important causes of preventable hearing loss, particularly in developing countries. Within the Global Burden of Diseases, Injuries, and Risk Factors Study, for the year 2005 we estimated the incidence of acute OM, chronic suppurative OM, and related hearing loss and mortality for all ages and the 21 WHO regional areas. Methods We identified risk factors, complications and sequelae of OM. We carried out an extensive literature review (Medline, Embase, Lilacs and Wholis) which lead to the selection of 114 papers comprising relevant data. Data were available from 15 of the 21 WHO regions. To estimate incidence and prevalence for all countries we adopted a two stage approach based on risk factors formulas and regression modelling. Results Acute OM incidence rate is 10.85% i.e. 709 million cases each year with 51% of these occurring in under-fives. Chronic suppurative OM incidence rate is 4.76 ‰ i.e. 31 million cases, with 22.6% of cases occurring annually in under-fives. OM-related hearing impairment has a prevalence of 30.82 per ten-thousand. Each year 21 thousand people die due to complications of OM. Conclusions Our study is the first attempt to systematically review the available information and provide global estimates for OM and related conditions. The overall burden deriving from AOM, CSOM and their sequelae is considerable, particularly in the first five years of life and in the poorest countries. The findings call for incorporating OM-focused action within preventive and case management strategies, with emphasis on the more affected.